Investigation of Wireless Body Area Network Localization Based on Measurement Data - Promwong, Sathaporn; Khongsomboon, Khamphong; Chaisang, Aditep (My University, 2022)
Short-range wireless communication is important for application use in wireless medical monitoring systems and wireless body area network localizations. Therefore, the channel's characteristics and the human body effect must be studied. This paper will investigate the wireless body area network localization and ZigBee technology based on the IEEE 802.15.4. Moreover, model wireless body area network measurement using a vector network analyzer at the frequency range of 2.2 GHz to 2.6 GHz for measurement and recording. In the experiment result, the wireless body area network localization is analyzed and evaluated by considering the received signal strength and distance error shown in the cumulative distribution function based on the CLEAN algorithm. From experimental studies, this project is beneficial for development studies and essential information for future research studies of wireless body area network localization applications.
Keywords: CLEAN algorithm; fingerprinting technique; indoor localization; WBAN; Zigbee